A Comparative Study of Community-Based Tourism Models and Environmental Outcomes in West Sumatra - Naufal Hibatullah; Rizki Sumardani; Ayang Khairunnisa (Jayapangus Press, 2026)
This study aims to analyze the implementation of Community-Based Tourism (CBT) in tourist destinations in West Sumatra and assess its impact on environmental conservation, local economic dynamics, and community resilience to climate change. There is a fundamental research gap in the study of Community-Based Tourism (CBT) in West Sumatra, namely the absence of an approach that simultaneously integrates environmental conservation, climate change mitigation, and local economic dynamics into one comprehensive framework. This study also identifies the key success factors and major obstacles in CBT management from the perspectives of communities, tourism stakeholders, and government institutions. The research method employs a qualitative approach using a comparative case study design across several community-based destinations in West Sumatra. Data collection was conducted through in-depth interviews, field observations, focus group discussions (FGDs), and analysis of policy documents and destination management reports. Research informants were selected using purposive sampling, involving destination managers, tourism awareness groups, MSME operators, local governments, and community leaders. The Research findings indicate that the implementation of CBT in West Sumatra still shows variations in community participation levels, the institutional capacity of local villages, and the quality of destination management. Several destinations have demonstrated success in enhancing local economic empowerment, strengthening cultural identity, and promoting environmental conservation practices through community education and participation. However, various challenges remain, such as limited human resource capacity, weak inter-institutional coordination, unequal distribution of economic benefits, and pressure on ecosystems due to increased tourism activities.